Respiratory distress syndrome management in resource limited settings—Current evidence and opportunities in 2022 - Ekhaguere, Osayame A.; Okonkwo, Ikechukwu R.; Batra, Maneesh; Hedstrom, Anna B. (Frontiers in Pediatrics, 2022)
The complications of prematurity are the leading cause of neonatal mortality worldwide, with the highest burden in the low- and middle-income countries of South Asia and Sub-Saharan Africa. A major driver of this prematurity-related neonatal mortality is respiratory distress syndrome due to immature lungs and surfactant deficiency. The World Health Organization’s Every Newborn Action Plan target 80% of districts have resources available to care for small and sick newborns, including premature infants with respiratory distress syndrome. Evidence-based interventions for respiratory distress syndrome management exist for the peripartum, delivery and neonatal intensive care period- however, cost, resources, and infrastructure limit their availability in low- and middle-income countries. Existing research and implementation gaps include the safe use of antenatal corticosteroid in non-tertiary settings, establishing emergency transportation services from low to high level care facilities, optimized delivery room resuscitation, provision of affordable caffeine and surfactant as well as implementing non-traditional methods of surfactant administration. There is also a need to optimize affordable continuous positive airway pressure devices able to blend oxygen, provide humidity and deliver reliable pressure. If the high prematurity related neonatal mortality experienced in low- and middle-income countries is to be mitigated, a concerted effort by researchers, implementers and policy developers is required to address these key modalities.